Enhancing Product Excellence and Business Growth Approaches for Small and Medium-Sizes Pastry and Bakery Enterprises: A case of Widhy’s Cake and Bakery Lampung - Wawan Bagus Santoso; Wuryaningsih Dwi Sayekti; Dyah Aring Hepiana Lestari (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2023)
TThis research aims to comprehensively assess the production facilities, production performance, operating income, the marketing mix, supporting services, and strategy development within Small and Medium-Sized Enterprises (SMEs) in the pastry and bakery industry. The study includes 41 respondents, comprising business owners, seven employees, 30 consumers, and three expert chefs in the pastry and bakery field. A mixed-method approach, combining descriptive qualitative and quantitative analyses, was employed. The research involved both qualitative exploration of respondents' perceptions and quantitative measurements of production performance and marketing effectiveness. Findings revealed satisfactory product quality, yielding profitable results from an average daily production of 100 bread loaves and 32 cakes. While the overall marketing mix was effective, the promotional aspect was identified as an area requiring enhancement. Supporting services were underutilized, suggesting opportunities for improvement, particularly in optimizing raw material utilization to heighten productivity and income while ensuring superior product quality. The study underscores the need for strategic enhancements in promotional efforts and the maximization of supporting services to align with the already satisfactory product quality. Furthermore, it emphasizes the significance of leveraging raw materials effectively to augment productivity and profitability in the SMEs pastry and bakery sector. Enhancing promotional strategies and optimizing supporting services are crucial for SMEs in the pastry and bakery industry to strengthen market positioning. Additionally, future research endeavors should delve deeper into the impact of optimized raw material utilization on productivity and income within this sector, thereby fostering sustained growth and competitiveness.